2012
DOI: 10.1890/es12-00062.1
|View full text |Cite
|
Sign up to set email alerts
|

Footprint of recycled water subsidies downwind of Lake Michigan

Abstract: Abstract. Continental evaporation is a significant and dynamic flux within the atmospheric water budget, but few methods provide robust observational constraints on the large-scale hydroclimatological and hydroecological impacts of this 'recycled-water' flux. We demonstrate a geospatial analysis that provides such information, using stable isotope data to map the distribution of recycled water in shallow aquifers downwind from Lake Michigan. The d 2 H and d 18O values of groundwater in the study region decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 48 publications
6
64
0
Order By: Relevance
“…Based on monthly precipitation, the annual weighted contribution of evaporation was calculated to be 23.42% or 90.54 mm/year. These results indicated that there is plentiful evaporation from the lake to mix with vapor from the upwind region and increase the d-excess value of local precipitation in the basin (Froehlich et al, 2008;Xu et al, 2011;Bowen et al, 2012). The contribution of evaporation was similar to the results of previous similar studies ( Table 4).…”
Section: Contribution Of the Evaporation From Lake To Local Precipitasupporting
confidence: 88%
See 2 more Smart Citations
“…Based on monthly precipitation, the annual weighted contribution of evaporation was calculated to be 23.42% or 90.54 mm/year. These results indicated that there is plentiful evaporation from the lake to mix with vapor from the upwind region and increase the d-excess value of local precipitation in the basin (Froehlich et al, 2008;Xu et al, 2011;Bowen et al, 2012). The contribution of evaporation was similar to the results of previous similar studies ( Table 4).…”
Section: Contribution Of the Evaporation From Lake To Local Precipitasupporting
confidence: 88%
“…Lake effect is represented by the relationships between the δ 18 O of precipitation and the distance between the sampling location and lake center (Fig. 1, Haixin Mountain), to explore the influence of evaporation from the lake on the basin's total precipitation (Gat et al, 1994;Bowen et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that water vapor deuterium excess (d = δ 2 H -8 × δ 18 O) closely tracks changes in CO 2 through inversion events and across a daily cycle dominated by patterns of human activity. Deuterium excess reflects deviations in the coupled H and O isotopic compositions of water from a covariant trend established by equilibrium phase-change reactions in the atmosphere, and has previously been used to diagnose vapor source region conditions, nonequilibrium processes, and vertical mixing (18)(19)(20)(21). We demonstrate that combustion-derived water vapor is characterized by a distinctive d value due to its unique mode of production, illustrate that this strong signal is detectible and can be used to quantify the concentration of combustion-derived vapor in the SLC wintertime atmosphere, and demonstrate congruence between these estimates and those derived from a mass-balance model forced by meteorological and emissions data.…”
mentioning
confidence: 99%
“…Tools such as IsoMAP (Bowen et al ) allow users to generate isoscapes that have unique spatial and temporal domains relevant to the study (Bowen et al , Vander Zanden et al , Tonra et al ). However, the distribution of GNIP measurements that comprise the majority of the data available is variable in time and space (Aggarwal et al ).…”
mentioning
confidence: 99%